Konstruk Psikologis dalam Tradisi Karapan Sapi di Madura: Solidaritas, Kompetitivitas, Harga Diri, Identitas, dan Keberanian - Rahmah Amaliya; Marselius Sampe Tondok (EduInovasi: Journal of Basic Educational Studies, 2025)
Research on Psychological Constructs in the Karapan Sapi Tradition in Madura: Solidarity, Competitiveness, Self-Esteem, Identity, and Courage aims to gain a deeper understanding of the psychological constructs that emerge in the Karapan Sapi tradition in Madura. The method used in this research is the descriptive exploratory qualitative method through literature study, namely the method of collecting data by understanding and studying theories from various literature related to research. This research shows the results that Karapan Sapi becomes a symbol of unity, solidarity, and identity for the Madurese people while creating a competitive drive between cow owners, jockeys, and spectators.